Klavirska dela Janka Ravnika, objavljena v Novih akordih - Bogunović Hočevar, Katarina (Muzikološki zbornik, 2010)
Janko Ravnik was, when entering the Slovene musical scene, considered to be (beside Marij Kogoj) a promising composer. Special attention in the New Chords was drawn by his piano works, which, according to contemporary criticism, was opening a new chapter in Slovene piano music. The article dealswith the compositional structure of pieces published in the New Chords, from which the characteristics of the composer's poetics in his early piano compositions are deduced.
Keywords: glasbena analiza; klavirska dela; musical analysis; Novi akordi (periodika); piano works; Ravnik, Janko, 1891-1982